The perception of non-Muslim tourists towards halal tourism: Evidence from Turkey and Malaysia - Battour, M; Hakimian, F; Ismail, M; Bogan, E (Emerald Group Publishing Ltd, 2024)
Indexed by WOS/SCOPUS/ERA